The effect of rehabilitative exercises accompanied by aids to improve muscle strength and range of motion for people with dislocated shoulder joint - Riam Imad Dr. Huda Badawi (physical education and sport sciences college for women/ Baghdad University, 2020)
The research aims to: Preparing rehabilitative exercises with accompanying tools to rehabilitate those with shoulder dislocation. Knowing the effect of rehabilitative exercises and accompanying aids in improving the muscular strength and motor range of those with dislocations in the shoulder joint. The two researchers used the experimental design with the same experimental group with the pre and post tests, so the researcher chose a sample appropriate to the nature of his research problem, its goals and its hypotheses, as a sample of the injured was chosen to remove the shoulder joint, who completed the treatment, who were not practicing sports, and those who went to the Physiotherapy Center at Al-Wasiti Hospital, as their number reached (10) were injured. A group of rehabilitative exercises was prepared and accompanied by auxiliary tools presented to experts and specialists in the field of sports medicine. Pre-test tests were conducted and then rehabilitative exercises were implemented to achieve the desired goal of the research. The number of rehabilitative units was 3 rehabilitative units per week and for days Sunday, Tuesday, Thursday. For a period of eight weeks, i.e. at the rate of 24 rehabilitative units and then conducting post-test. The researchers concluded the following: _ Rehabilitation exercises prepared by the two researchers with a clear positive effect on improving muscle strength and motor range among the individuals in the research sample. _ The auxiliary tools used by the two researchers have a positive effect in stimulating and provoking motivation and suspense among the injured to perform rehabilitative exercises. The researchers recommended: - To conduct similar research on other injuries and different samples and to adopt the rehabilitation approach by the two researchers in other physiotherapy centers.